2011
DOI: 10.1017/s0007114511004405
|View full text |Cite
|
Sign up to set email alerts
|

Respective contributions of intestinal Niemann-Pick C1-like 1 and scavenger receptor class B type I to cholesterol and tocopherol uptake:in vivov.in vitrostudies

Abstract: The intestinal absorption of cholesterol and lipid micronutrients such as vitamin E has been shown to share some common pathways. The present study aims to further compare the uptake of cholesterol ([ 3 H]cholesterol v. 22-(N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino)-23,24-bisnor-5-cholen-3-ol (NBD-cholesterol)) and tocopherol in Caco-2 TC-7 cells and in mouse intestine, with special focus on the respective roles of scavenger receptor class B type I (SR-BI) and Niemann-Pick C1-like 1 (NPC1L1). Conversely to NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 40 publications
6
50
0
Order By: Relevance
“…Moreover, accordingly to our SPR data showing that free OA and DHA were SR-BI ligands, mice overexpressing SR-BI at the A key fi nding is that these structures mimicking mixed micelles, i.e., including various lipids and lipid digestion products, are necessary for optimal binding to both lCD36 and lSR-BI. This is consistent with previous results showing that SR-BI could bind postprandial but not interprandial micelles ( 13 ), and that cholesterol uptake from simple micelles was unaffected by the addition of SR-BI inhibitor, in contrast to cholesterol uptake from mixed micelles ( 34 ).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, accordingly to our SPR data showing that free OA and DHA were SR-BI ligands, mice overexpressing SR-BI at the A key fi nding is that these structures mimicking mixed micelles, i.e., including various lipids and lipid digestion products, are necessary for optimal binding to both lCD36 and lSR-BI. This is consistent with previous results showing that SR-BI could bind postprandial but not interprandial micelles ( 13 ), and that cholesterol uptake from simple micelles was unaffected by the addition of SR-BI inhibitor, in contrast to cholesterol uptake from mixed micelles ( 34 ).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Chol-NBD (22-N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)-amino)-23,24-bisnor-5-cholen-3β-ol) is reported to be absorbed via NPC1L1-independent pathway. 16,17) In terms of cholesterol uptake via NPC1L1, it has been reported that the N-terminal domain of NPC1L1 binds cholesterol and promotes formation of cholesterol-enriched membrane microdomains comprising lipid raft proteins flotillin-1 and flotillin-2. 8,18) Clathrin is then recruited to internalize the NPC1L1-flotillin-cholesterol membrane microdomains.…”
Section: Effect Of Cholesterol In Lipid Emulsion Particles On the Uptmentioning
confidence: 99%
“…We also consider that further studies are needed to clarify the recognition of cholesterol and its related-substances, substrates of NPC1L1, as Reboul et al also suggested that the chemical modification from cholesterol to NBD-Chol has a real impact in NPC1L1 recognition. 17) We then investigated how lipid emulsion particles themselves were incorporated into Caco-2 cells as well as cholesterol (Fig. 3).…”
Section: Effect Of Cholesterol In Lipid Emulsion Particles On the Uptmentioning
confidence: 99%
“…Apparently, cystic fi brosis impedes vitamin E absorption only in those individuals with impaired bile secretion, suggesting that the requirement for gastrointestinal lipase is not as great as that for bile acids ( 25,26 ). The minimum requirements for vitamin E absorption have been reported as its incorporation into micelles containing taurocholate and oleic acid ( 27 ). It is unclear whether these components function to solubilize vitamin E for its uptake into enterocytes or whether they function as ligands for specifi c receptors for internalization of the micelle.…”
Section: Hepatic Secretion Of ␣ -Tocopherol Into Plasmamentioning
confidence: 99%
“…Additionally, the scavenger receptor B-1 (SR B-1) has been shown to facilitate both cholesterol and tocopherol uptake into enterocytes and to be inhibited by a specifi c SR B-1 inhibitor, block lipid transport-1 (BLT-1) ( 27,29 ). However, when evaluated in vivo, cholesterol and tocopherol absorption by mice occurred in quite different locations, with the greatest tocopherol absorption in the distal jejunum, suggesting there may be additional mechanisms/receptors/transporters involved in vitamin E absorption ( 27 ).…”
Section: Hepatic Secretion Of ␣ -Tocopherol Into Plasmamentioning
confidence: 99%